2018
DOI: 10.3390/en11010135
|View full text |Cite
|
Sign up to set email alerts
|

A Free-Piston Linear Generator Control Strategy for Improving Output Power

Abstract: This paper presents a control strategy to improve the output power for a single-cylinder two-stroke free-piston linear generator (FPLG). The comprehensive simulation model of this FPLG is established and the operation principle is introduced. The factors that affect the output power are analyzed theoretically. The characteristics of the piston motion are studied. Considering the different features of the piston motion respectively in acceleration and deceleration phases, a ladder-like electromagnetic force con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…When the FPLG has two cylinders, the piston motion is mainly controlled by LEM during the starting process. Some studies focused on the starting process using position feedback or the constant-magnitude motoring force approach [37,[42][43][44][45]. In order to obtain a desired piston trajectory, the position error serves as a feedback variable to control the thrust force with appropriate value and direction [43].…”
Section: Atarting Methods Of Fplgsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the FPLG has two cylinders, the piston motion is mainly controlled by LEM during the starting process. Some studies focused on the starting process using position feedback or the constant-magnitude motoring force approach [37,[42][43][44][45]. In order to obtain a desired piston trajectory, the position error serves as a feedback variable to control the thrust force with appropriate value and direction [43].…”
Section: Atarting Methods Of Fplgsmentioning
confidence: 99%
“…More importantly, it will affect the compression process, scavenging process, combustion quality, and further produce cycle-to-cycle variations. In particular, under limiting operation conditions such as the dead positions, piston displacement and velocity, the state of reciprocation motion depends on the input and output energy conversion [37,38]. Where the input energy is from fuel burning and the output energy is produced by the resultant force in a cycle.…”
Section: Piston Motion Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve relatively high quality and efficiency for converting ocean wave energy into electrical energy, various ocean wave energy converters and corresponding electrical machines have been investigated. It was found that linear generators can be used in the direct drive wave energy conversion system, in which it can reduce the complexity of mechanical transmission and improve the reliability and efficiency of the system [6][7][8][9][10][11]. Several electrical generator topologies have been analyzed in the past years [12,13].…”
Section: Introductionmentioning
confidence: 99%